TIPE KEPEMIMPINAN DEMOKRATIS KEPALA MADRASAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU - Moh . Nasir; Bulu' K .; Mahadin Shaleh (Kelola: Journal of Islamic Education Management, 2021)
This research aimed at analyzing the leadership model of madrasah principle in improving the professional competence of educators, efforts made as well as strategies implemented in schools in order to improve the professionalism of Islamic Education teachers in Madrasah Aliyah Sohifatussofa Nahdlatul Wathan Rawamangun North Luwu Regency. This research used a qualitative approach with this type of case study, as well as a psycho-individual-cultural approach and an institutional approach.  Data collection used interview, observation, and documentation techniques. As for data analysis techniques, researchers used interactive analysis models containing four interconnected components, namely: data collection, data simplification, data exposure, and withdrawal and submission of summations. Checking the validity of findings was carried out with credibility, transferability, dependability, and affirmability, using a variety of sources, theories, and methods so that objective data is obtained. The results shows that: (1) The leadership of the madrasah principle at MA Sohifatussofa NW Rawamangun has characteristics of the democratic leadership model with: a) Having an emphasis in terms of structuring clear vision and mission, communicating the vision effectively and implementing that vision. b) The principle of madrasah has leadership values that are the foundation of thinking and acting in leading madrassas namely: discipline in work; be democratic; responsible; dare to innovate; honest and open. c) The principle of the madrasah also has a well-established social relationship with the madrasah residents, among others: parallels; exemplary; appreciate achievements; kinship; Concern. The essence of Democratic leadership is to engage subordinates together to make changes. (2) Strategies used by madrasah principles in improving the professional competency of teachers at MA Sohifatussofa NW Rawamangun through further study, learning supervision, Teacher Deliberation of Subjects, comparative studies, workshops, and training.